Perceived urban green spaces and youth mental health in the post-COVID-19 era - Mollaesmaeili, Mahsa; Hakimian, Pantea; Lak, Azadeh (Frontiers in Public Health, 2024)
The urban green space (UGS) is one of the most significant urban spaces with unique visual and social features, including pleasant air, low noise, and vitality, making it a recreational place for citizens, especially the youth. According to previous studies, perceived green space and the interaction with it is associated with mental health and lower symptoms of anxiety and depression. Although the presence of urban and blue-green spaces in Isfahan has a long history, the UGSs have been out of reach, causing a significant impact on youth mental health due to the spread of COVID-19 and the forcing of the Iranian government to severe and long-term lockdown. This study investigates the relationship between the long-term isolation of youth and being away from UGSs on their mental health in Isfahan city. In September 2022, the youth (n=273) in 12 neighborhoods with similar socio-economic status were asked to answer the online questionnaire. To investigate the correlation between perceived UGS and the mental health of the youth, Structural Equation Modeling (SEM) is done. The results show that the perceived UGSs negatively relate to the youth's fear of the reoccurrence of COVID-19 infection, anxiety, and depression. Moreover, the model shows that perceived UGS has an inverse correlation with anxiety (β= -0.24, p=0.00), and no meaningful correlation exists with depression. These results point to a practical solution for designing UDGs in residential areas for youth according to their benefits for mental health during the epidemic era.